Kinerja PT Bank Pembiayaan Rakyat Syariah (BPRS) Amanah Bangsa Berdasarkan Maqashid Sharia Index (MSI) - Surayya Fadhilah Nasution; Andri Soemitra; Yenni Samri Juliati Nasution (ITB AAS INDONESIA Surakarta, 2023)
The research aims to explain and analyze about PT BPRS Amanah Bangsa performance based on Maqashid Sharia Index. This research used quantitative descriptive approach with secondary data obtained from Sharia Rural Bank financial report that was published by OJK in ojk.go.id website period 2018 – 2020. Data analysis technique that was used in this research is Simpel Additive Weighting method with Multiple Attribute Decision Making approach. The research used three concepts, namely educating individual, establishing justice, and promoting welfare. MSI element that was used in this research, such as education grant, research, training, publicity, fair returns, functional distribution, interest free product, profit ratios, personal income, and investment ratios in real sector. The result of this research showed that PT BPRS Amanah Bangsa hasn’t been maximized because there’re some indicators of MSI hasn’t been implemented by the Sharia Rural Bank. The MSI average value of PT BPRS Amanah Bangsa is 0.0629.